Development of an Advanced Multicellular Intestinal Model for Assessing Immunomodulatory Properties of Anti-Inflammatory Compounds - Marescotti, Diego; Lo Sasso, Giuseppe; Guerrera, Diego; Renggli, Kasper; Ruiz Castro, Pedro A.; Piault, Romain; Jaquet, Vincent; Moine, Fabian; Luettich, Karsta; Frentzel, Stefan; Peitsch, Manuel C.; Hoeng, Julia (Frontiers in Pharmacology, 2021)
Intestinal inflammation is the collective term for immune system-mediated diseases of unknown, multifactorial etiology, with often complex interactions between genetic and environmental factors. To mechanistically investigate the effect of treatment with compounds possessing immunomodulating properties in the context of intestinal inflammation, we developed an immunocompetent in vitro triculture intestinal model consisting of a differentiated intestinal epithelial layer (Caco-2/HT29-MTX) and immunocompetent cells (differentiated THP-1). The triculture mimicked a healthy intestine with stable barrier integrity. Lipopolysaccharide treatment triggered a controlled and reversible inflammatory state, resulting in significant impairment of barrier integrity and release of pro-inflammatory cytokines and chemokines, which are known hallmarks of intestinal inflammation. Treatment with known anti-inflammatory reference compounds (TPCA-1 and budenoside) prevented the induction of an inflammatory state; the decreasing triculture responses to this treatment measured by cytokine release, transepithelial electric resistance (TEER), and epithelial layer permeability proved the suitability of the intestinal model for anti-inflammatory drug screening. Finally, selected tobacco alkaloids (nicotine and anatabine (R/S and S forms)) were tested in the in vitro triculture for their potential anti-inflammatory properties. Indeed, naturally occurring alkaloids, such as tobacco-derived alkaloids, have shown substantial anti-inflammatory effects in several in vitro and in vivo models of inflammation, gaining increasing interest. Similar to the anti-inflammatory reference compounds, one of the tobacco alkaloids under investigation partially prevented the decrease in the TEER and increase in permeability and reduced the release of pro-inflammatory cytokines and chemokines. Taken together, these data confirm that our in vitro model is suitable for screening potential anti-inflammatory compounds in the context of intestinal inflammation.